Assessment of Carbon Storage Potential and Economic Value in Green Open Space Vegetation of Palopo City - B.P, Andi Utami; Witno, Witno; Defara, Desya (Jurnal Penelitian Kehutanan BONITA, 2025)
Green open space (RTH) plays an essential role in climate change mitigation through its capacity to absorb and store carbon. Palopo City, which has experienced rapid urban growth, requires scientific data on carbon storage potential in its green open spaces. This study aimed to analyze carbon storage potential and the economic value of carbon in RTH vegetation in Palopo City. The research was conducted in selected RTH areas across nine districts using a non-destructive sampling method and allometric equations. Vegetation biomass was estimated from tree diameter measurements and converted into carbon storage and CO₂ absorption. Carbon economic value was calculated using carbon pricing estimates of USD 5–10 per ton. The results showed that total carbon storage in Palopo City’s RTH reached 9,094.93 tons/ha, with the highest value found in the Salubulo Islamic Cemetery RTH, North Wara District. This location also exhibited the highest carbon economic value. These findings highlight the strategic role of urban green open spaces in climate change mitigation and sustainable urban development).